2008
DOI: 10.1159/000163058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor Board Recommendations on Treatment Outcome for Locally Advanced Head and Neck Cancer

Abstract: Background/Aims: To identify physician selection factors in the treatment of locally advanced head and neck cancer and how treatment outcome is affected by Tumor Board recommendations. Methods: A retrospective analysis of 213 patients treated for locally advanced head and neck cancer in a single institution was performed. All treatments followed Tumor Board recommendations: 115 patients had chemotherapy and radiation, and 98 patients received postoperative radiation. Patient characteristics, treatment toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 58 publications
0
29
2
Order By: Relevance
“…A limited number of studies assessed impact of mccs on patient outcomes [4][5][6]15,23,29 . The common conclusion drawn was that multidisciplinary clinics and mdts are associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies assessed impact of mccs on patient outcomes [4][5][6]15,23,29 . The common conclusion drawn was that multidisciplinary clinics and mdts are associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…All studies concluded that a multidisciplinary setting resulted in improved patient outcomes in terms of diagnosis and/or treatment planning [14][15][16][18][19][20][21][22][25][26][27][28][29][31][32][33][35][36][37]40,42], improvements in survival [15,17,21,23,[28][29][30]36,39,41], patient satisfaction [24,31,38] and clinician satisfaction as a consequence of teamwork communication and cooperation [15,34]. Evidence of improved survival was found for colorectal [15,17,28,36], head and neck [29,41], breast [39], oesophageal [21] and lung [30] cancer.…”
Section: Impact On Patient Outcomesmentioning
confidence: 99%
“…The studies documented two motivating principles: firstly, MDTs ensure more appropriate treatment through a preoperative review of imaging and pathology results [19,20,22,25,26,40,42]; and secondly, a multidisciplinary approach guarantees the most up-todate treatment for all cancer patients seen at the facility or discussed online [16,18,21,23,32,33,35,[38][39][40][41]53]. Other clinical-based goals included improving patients' quality of life [24,32,42,[53][54][55] and setting up a structured followup care plan [53,[59][60][61].…”
Section: Mdt Goals and Scope Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Case presentation at HnN MDT affects and changes the clinical staging and therefore improves outcomes in a significant number of patients and improves quality of survival [19][20][21]. Because head and neck cancer is rare and complex, it has been suggested that advanced stage disease surgery should only be performed in high volume hospitals which will result in a shorter hospital stay, a better long-term survival and cure-rate [22][23][24].…”
mentioning
confidence: 99%